Steel plate sharpening machine - ZHU HAILIN; WU JUN; FAN CHENBIN; ZHU ZHAODONG; MIAO SHENGLONG (2023)
The invention relates to the technical field of machining, in particular to a steel plate sharpening machine which is characterized in that two side grinding rings are fixedly connected to the side surface of a second grinding roller, two side grinding grooves are formed in the side surface of a first grinding roller, and an adjusting bin is movably mounted at the top of a supporting bottom box; a motor plate is arranged on one side of the adjusting bin, a fixed motor is installed on the top of the motor plate, the two fixed sliding blocks are clamped into the positioning sliding grooves, two opposite threads are arranged on the side portion of the fixed shaft and are in threaded connection with the fixed sliding blocks, and two scale columns are fixedly connected into the adjusting bin; one side of the clamping frame is fixedly connected with a scale finger block; according to the steel plate sharpening machine, through cooperation of the sharpening mechanism and the adjusting mechanism, the surface and the